Aproximações entre humanidades digitais e organização do conhecimento - Andrade, Laura Mariane de (Universidade Federal de São Carlos, 2021)
In the last decades, a new field of research has emerged and has been consolidated, namely the Digital Humanities that, in the integration of traditional Human Sciences in digital environments, determine their particularities by renewing the humanistic praxis. Due to their transdisciplinarity character, debates involving Digital Humanities in Information Science have been increasingly stimulated, as they can contribute to the resources understanding and appropriation, making both areas interrelated under an emerging theme for Information Science, ideally in Knowledge Organization. In order to identify how studies in the Knowledge Organization universe incorporate digital technologies added to the humanities, the purpose is to present a study on scientific configuration of Knowledge Organization that works with the Digital Humanities from Science of Information, more specifically (1) identifying the presence of Digital Humanities in Information Science and their approach to themes of Knowledge Organization; (2) rescuing the Knowledge Organization as an interdisciplinary field of knowledge and às an investigative space for issues related to content in the digital environment representation; and (3) analyzing the scenario presented by international scientific papers with the help of Iramuteq software and how the most consistent studies in Knowledge Organization reveal the Digital Humanities absorption. For that, we resort to bibliographic research, collection, application of the Iramuteq software to obtain textual analysis in 96 papers abstracts collected from international databases with scope of Digital Humanities and Knowledge Organization, and, finally, a qualitative analysis of 25 papers from one of the classes identified by the software closest to the research proposal. The analysis reveals the terminological insertion of Digital Humanities in discussions inherent to Knowledge Organization is not scarce, however such researchers find it difficult to theorize, discuss and appropriate epistemological domains of Knowledge Organization and Digital Humanities. We conclude that initiatives consistency that link Digital Humanities to the object of investigation of information scientists seems to be a consensus for appropriation by the Knowledge Organization and establishment of Digital Humanities in their context, especially in a society increasingly mediated by digital.
Approaches between digital humanities and knowledge organization
Keywords: Humanidades digitais; Organização do conhecimento; Transdisciplinaridade; Digital humanities; Knowledge organization; Transdisciplinarity; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO